Combustion Process of Coal–Açai Seed Mixtures in a Circulating Fluidized Bed Boiler - Gabriel C. P. Soares; João V. R. Moreira; Fernando H. B. Santos; Danielle R. S. Guerra; Manoel F. M. Nogueira (Energies)
This study investigates the effects of the co-combustion of coal and açai seed in circulating fluidized bed (CFB) boilers, highlighting the increase in thermal efficiency and relevance of a less-polluting source of energy. Using the computer software 1.5D CeSFaMB™® v4.3.0, simulations of the co-combustion process of coal and biomass were carried out in a CFB boiler, obtaining results such as the temperature profile, boiler efficiency and emissions. The work acquired data regarding the equipment in real operational conditions, consisting of the fundamental geometric and operational parameters used in the simulation campaign. The thermal and chemical properties of the fuels were analyzed by carrying out proximate, ultimate, heating value, particle size and specific mass analyses. The model validation was achieved by simulating the boiler in its real operating conditions and comparing the obtained results with the real data; the obtained error was below 10%. Simulations with different fractions of açai seed for energy replacement (10% and 30%) were carried out. As a result, an increase in the average temperature of the bed was observed, highlighting the region immediately above the dense bed. An increase in boiler efficiency was verified from 56% to 85% with 10% açai and to 83% with 30% açai seed. Decreases in SO2 and CO emissions with the insertion of açai were obtained, showing that co-combustion is more complete, while CO2 emissions were increased due to the higher quantity of fuel inserted into the equipment. The fossil CO2 emissions were reduced.